Ways of improvement of radiation techniques for the qualification of Nuclear Power Plants' equipment - T. V. Kovalinska; I. A. Ostapenko; V. I. Sakhno; A. G. Zelinskyy (Ядерна фізика та енергетика)
Ways of the improvement of technical base of the INR of NAS of Ukraine for functional researches and new technologies of control over the state of the equipment on NPPs are discussed. The scientific work is completed in the department of radiation technologies within the national program of the enhancement of the reliability of nuclear energetic and the prolongation of operation terms of nuclear power installations.